Phytoremediation: Sustainable Solutions for Heavy Metal Pollution and Bioenergy in Bangladesh - Md Nasir Ahmed; Chowdhury Alfi Afroze; Rownak Jahan (The Scientific World Journal)
Heavy metal pollution is plundering the well-being of people in Bangladesh, a developing country in South Asia, which is also striving to secure green energy resources. This comprehensive review highlights the use of phytoremediation technology to both clean up heavy metal pollution and produce bioenergy in Bangladesh. It emphasizes the dual benefits of removing contaminants from the environment while generating sustainable energy sources. We identified 16 species of hyperaccumulators with potential as bioenergy sources, including second-generation bioethanol, biodiesel, biofuels, biogas, and bioelectricity. This effort supports the adaptability of Sustainable Development Goal 7—access to affordable, reliable, sustainable, and modern energy for all—and is aimed at helping Bangladesh achieve its target of generating 15% of total electricity from renewable sources by 2041. These species were effective in accumulating heavy metals from contaminated soils and wastewater. Bioenergy plants with hyperaccumulating activities can address the issue of biomass disposal by converting bioenergy production after the remediation process of chemical pollutants, leading to bioeconomic technology and increasing the acceptance of large-scale applications. Using advanced biotechnological approaches, it is possible to improve hyperaccumulating activities such as absorbing, accumulating, biodegrading, or immobilizing heavy metals. The review further provides recommendations, including funding initiatives, public awareness campaigns, collaborative efforts, policy development, and capacity building to enhance the development and implementation of phytoremediation technology using bioenergetic plants in Bangladesh, thereby unlocking its bioeconomic potential.